2008
DOI: 10.1177/1753425907088243
|View full text |Cite
|
Sign up to set email alerts
|

Removal of immune-stimulatory components from surfaces by plasma discharges

Abstract: Immune-stimulating microbiological components like lipopolysaccharide (LPS), lipoteichoic acid (LTA) and zymosan bound onto surfaces lead to severe problems when brought in contact with the organism via surgical instruments or implants. We have shown, in recent studies, that it is possible to detect different immune-stimulating components directly on the surface, via an indirect detection method, using human whole-blood and the monocyte reaction to measure the inflammatory mediator release (IL-1beta) by ELISA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Nevertheless, those pioneering studies clearly demonstrated the possibility to eliminate different proteins [14, 20, 21, 23-25, 28, 45, 46] and bacterial endotoxins [15,[17][18][19]45] from surfaces by plasma treatment and reported chemical and morphological changes of the treated biomolecules induced by plasma discharges. Those studies also indicated that effective elimination of biomolecules can be achieved preferably within an active plasma sustained in oxygen-containing discharge mixtures.…”
Section: Effect On Biomoleculesmentioning
confidence: 98%
“…Nevertheless, those pioneering studies clearly demonstrated the possibility to eliminate different proteins [14, 20, 21, 23-25, 28, 45, 46] and bacterial endotoxins [15,[17][18][19]45] from surfaces by plasma treatment and reported chemical and morphological changes of the treated biomolecules induced by plasma discharges. Those studies also indicated that effective elimination of biomolecules can be achieved preferably within an active plasma sustained in oxygen-containing discharge mixtures.…”
Section: Effect On Biomoleculesmentioning
confidence: 98%
“…In former experiments with a remote microwave post discharge, it had been impossible to inactivate PGN films even for a duration treatment of 30 min while other pyrogens (LPS or lipid A) obtained from different bacterial strands could be inactivated or removed easily in 10 min or less [37]. However, the results of imaging ellipsometry depicted in Fig.…”
Section: Bacterial Spores and Bacterial Endotoxinsmentioning
confidence: 91%
“…The efficiency of the plasma treatment in terms of etching of biomolecules has been studied on PGN, representative of highly resistant bacterial endotoxins [37], on lipid A, which constitutes pyrogenic entities of lipopolysaccharides, as well as on bovine serum albumin (BSA) that has been selected as a model protein. The samples were prepared by spotting small droplets of 0.1 % aqueous solution of these substances on polished Si wafers.…”
Section: Coating Of Bacterial Endotoxins and Proteinmentioning
confidence: 99%
“…And although recent research on the use of plasma exposure to inactivate endotoxin shows promise for the future (Shintani et al ., 2007;Hasiwa et al ., 2008), currently available low-temperature plasma technology sterilizers may not have the same source gas for plasma generation as that used in research (i.e. nitrogen vs hydrogen peroxide) and may not be validated for endotoxin inactivation.…”
Section: Endotoxin Removal Strategies and Sterilization Processesmentioning
confidence: 95%